Metabolic demands and replenishment of muscle glycogen after a rugby league match simulation protocol - Bradley, W. J.; Hannon, M. P.; Benford, V.; Morehen, J. C.; Twist, C.; Shepherd, S.; Cocks, M.; Impey, S. G.; Cooper, R. G.; Morton, J. P.; Close, G. L. (Journal of Science and Medicine in Sport, 2017)
Objectives: The metabolic requirements of a rugby league match simulation protocol and the timing of carbohydrate provision on glycogen re-synthesis in damaged muscle were examined. Design: Fifteen (mean ± SD: age 20.9 ± 2.9 year, body-mass 87.3 ± 14.1 kg, height 177.4 ± 6.0 cm) rugby league (RL) players consumed a 6 g kg day-1 CHO diet for 7-days, completed a time to exhaustion test (TTE) and a glycogen depletion protocol on day-3, a RL simulated-match protocol (RLMSP) on day-5 and a TTE on day-7. Players were prescribed an immediate or delayed (2-h-post) re-feed post-simulation. Methods: Muscle biopsies and blood samples were obtained post-depletion, before and after simulated match-play, and 48-h after match-play with PlayerLoad and heart-rate collected throughout the simulation. Data were analysed using effects sizes ± 90% CI and magnitude-based inferences. Results: PlayerLoad (8.0 ± 0.7 AU min-1) and %HRpeak (83 ± 4.9%) during the simulation were similar to values reported for RL match-play. Muscle glycogen very likely increased from immediately after to 48-h post-simulation (272 ± 97 cf. 416 ± 162 mmol kg-1d.w.; ES ± 90%CI) after immediate re-feed, but changes were unclear (283 ± 68 cf. 361 ± 144 mmol kg-1d.w.; ES ± 90%CI) after delayed re-feed. CK almost certainly increased by 77.9 ± 25.4% (0.75 ± 0.19) post-simulation for all players. Conclusions: The RLMSP presents a replication of the internal loads associated with professional RL match-play, although difficulties in replicating the collision reduced the metabolic demands and glycogen utilisation. Further, it is possible to replete muscle glycogen in damaged muscle employing an immediate re-feed strategy.